Anti‐desmocollin autoantibodies in nonclassical pemphigus. (28th May 2015) - Ishii, N.; Teye, K.; Fukuda, S.; Uehara, R.; Hachiya, T.; Koga, H.; Tsuchisaka, A.; Numata, S.; Ohyama, B.; Tateishi, C.; Tsuruta, D.; Furumura, M.; et al.
<x xml:space="preserve">Abstract</x> What's already known about this topic? Despite the established pathogenic role of anti‐desmoglein (Dsg) antibodies in classical pemphigus, the significance of autoantibodies to another desmosomal cadherin, desmocollin (Dsc), is at present unknown. No consistent immunoassay for IgG autoantibodies to Dscs has been developed. What does this study add? We have successfully established new sensitive and specific mammalian Dsc immunoglobulin (Ig) G enzyme‐linked immunosorbent assays. Our data show that IgG anti‐Dsc autoantibodies are frequently detected and potentially pathogenic in particular types of nonclassical pemphigus.